Transcriptomic and metabolomic insights into neutrophil activity in COPD complicated by metabolic syndrome - Juan Li; Xue Wu; Yufen Fu; Jiliu Liu; Yao Liu; Jiahuan Li; Bomiao Qing; Yi Zhang; Jie Gao; Xiang He; Junyi Wang; Guoping Li (BioMedical Engineering OnLine)
Abstract Objectives Chronic obstructive pulmonary disease (COPD) frequently coexists with metabolic syndrome (MS), compounding its impact on patients’ health and quality of life. This study aimed to elucidate the immune and metabolic response characteristics in COPD patients with and without MS. Methods A total of 11,315 COPD patients admitted to the Department of Respiratory and Critical Care Medicine at the Third People’s Hospital of Chengdu between January 1, 2013, and May 1, 2023, were selected. Multivariate logistic regression was conducted to identify the risk factors for acute exacerbation of chronic obstructive pulmonary disease. Moreover, from this cohort, 30 patients (18 with COPD and 12 with COPD–MS) were recruited for a further study to investigate the underlying mechanisms of COPD and COPD–MS. Blood samples were collected from these participants to perform transcriptomic and metabolomic analyses, aiming to explore the differences in immune responses and metabolic alterations between the two groups. Results Our findings indicate a significant enhancement of neutrophil-mediated immune responses in COPD–MS patients. Transcriptomic analysis revealed 327 differentially expressed genes (DEGs) significantly involved in neutrophil-mediated immunity. Key metabolic pathways were disrupted, with 39 differential metabolites identified. Notably, metabolites, such as L-homoarginine and diethanolamine, which were elevated in COPD–MS patients, showed strong correlations with DEGs involved in neutrophil pathways and immune checkpoint regulation. The study also found decreased levels of IL4 and IL5RA in COPD–MS patients, suggesting a shift from Th2 to Th1 inflammatory responses, potentially contributing to glucocorticoid resistance. Conclusions COPD patients with metabolic syndrome exhibit a heightened neutrophil-mediated inflammatory response and significant metabolic disturbances, which underscores the need for precise therapeutic strategies targeting both metabolic and inflammatory pathways to improve patient outcomes and manage COPD–MS complexities effectively.